Les conditions d’exercice du travail des cadres de premier niveau : une étude de cas - François Bolduc; Geneviève Baril-Gingras (Perspectives Interdisciplinaires sur le Travail et la Santé)
First-level managers’ work has undergone many changes in recent years. In Québec’s public health network, the number of these managers has decreased significantly. However, they play an important role in the health (physical and mental) and safety of work team members, since they define some of their working conditions and some aspects of the psycho-social work environment. The aim of the study was to better understand first-level managers’ work and the influence of the conditions in which it is done. The study proceeded by observations of 12 managers’ work activity, in the form of work chronicles, and by interviews based on these observations. The article presents and discusses three types of results: some examples of how the prescribed task is converted into an effective task and of its translation into their work activity; a synthesis of how they perceive their role or "effective task"; and observations about the gap between this perception and their working conditions, in particular because of a quantitative work overload, limited actual autonomy, and obstacles to the planning and long-term development of their services. Therefore, these conditions do not seem favourable to the positive role they want to play and that is expected of them in relation to their work teams.